Landscape's physiognomic structure: conceptual development and practical applications. (3rd April 2018) - Chmielewski, Tadeusz J.; Butler, Andrew; Kułak, Agnieszka; Chmielewski, Szymon
Abstract: The past decade has seen an increased interest in approaches for the identification and assessment of landscapes, which has been, in part, a response to the European Landscape Convention (ELC). In this article, we review landscape physiognomy, an important component of the Polish approach to the assessment and identification of its landscape. We address the relevance of physiognomy both in relation to the ELC and to the landscape character assessments approach, and then explore the theoretical basis of landscape physiognomic structure. We also expand the existing classification of landscape interiors; this is followed by combining three approaches: (1) physical geography in the field of comprehensive classification of natural landscapes; (2) landscape ecology studies on the spatial structure of land cover patches against the 'landscape matrix' and (3) the theory of landscape interiors. Presented ideas create the outline of the concept of landscape's physiognomic structure.